Quantitative characterization of the multiscale mechanical properties of low-permeability sandstone roofs of coal seams based on nanoindentation and triaxial tests and its implications for CO2 geological sequestration - Feng Cao; Jianhua He; Hongxiu Cao; Hucheng Deng; Andrew D. La Croix; Rui Jiang; Ruixue Li; Jiarun Li (International Journal of Coal Science & Technology)
Abstract Microstructural heterogeneity of low-permeability sandstone roofs of deep unmineable coal seams due to diagenesis significantly affects rock mechanical behavior, greatly impacting the sealing potential of in situ CO2 sequestration and the structural stability of the geological formation. However, little is known about how the microstructure of different mineral groups influences the multiscale mechanical behavior of deep sandstone. This study proposes a new method for quantitatively characterizing the multiscale mechanical properties of low-permeability sandstone and shows the mechanisms responsible for mechanical failure at the micro-, meso-, and macroscale. Triaxial compression tests and targeted nanoindentation tests were conducted to assess the micro- and macroscale mechanical properties of different types of sandstone. The micro- and macroscale experiments were coupled with numerical simulations of compression using a unified cohesive model based on Voronoi polygons to clarify the multiscale mechanical behavior. The results indicate that quartz, the primary mineral component of the sandstones examined, exhibits the strongest micromechanical properties, followed by feldspar, calcite, and clay minerals. Compared to polycrystalline quartz, monocrystalline quartz has a more stable microstructure and is mechanically stronger. The macro-mechanical properties of tight sandstone samples are weakened by increased microstructural inhomogeneity and larger grain size. This leads to a higher likelihood of splitting damage, characterized by a high degree of discrete and weak stress sensitivity. The major conclusion is that the positive rhythm lithofacies of medium-grained sandstone to siltstone are the most favorable for efficient CO2 sequestration in deep unmineable coal seams.